Reducing EEG (Electroencephalogram) Electrode-induced Skin Injury among Ambulatory EEG Monitored Patients: A Non-randomized Interventional Study of Two Commonly Used Cream-based Products for Electrode Application. (1st October 2020) - Ouchida, Sumika; Nikpour, Armin; Fairbrother, Greg
ABSTRACT: Ambulatory electroencephalography (AEEG) seeks to capture inter-ictal epileptiform activity or paroxysmal events when patients are not in the clinic. Skin inflammation is a common complication of prolonged EEG monitoring. This non-randomized study aimed to investigate the performance of two commonly used cream-based methods of electrode application in reducing electrode-induced skin injury among patients undergoing AEEG monitoring. A non-randomized interventional study was conducted from July to December 2019 in the Neurosciences Ambulatory Care Unit at Royal Prince Alfred Hospital, Australia. Patients were enrolled into two groups: i) Group T, which received Ten20® Conductive Paste with Tensive® Conductive Adhesive Gel as the primary approach to electrode application; ii). Group E, which received EC2⁺® Conductive Cream as the primary approach to electrode application. Patients in Group T were enrolled in the 1st and 3rd week of the month, and patients in Group E were enrolled in the 2nd and 4th week for each month of the study. A total of 152 patients participated in this study. Two sub-groups were established: those who were monitored for two days (Group T; n = 36, Group E; n = 30) and those who were monitored for four days (Group T; n = 43, Group E; n = 43). Significant (p < 0.05) differences indicating greater inflammation in the Group E were noted for both Day 2 and Day 4 participants. Skin injury/inflammation was significantly less using the standard method (Group T: Ten20® with Tensive® gel) when compared to EC2⁺® (Group E) as the conductive material at the electrode site.